2020
DOI: 10.1111/jace.17390
|View full text |Cite
|
Sign up to set email alerts
|

Interface engineering of nanoceramic hematite photoelectrode for solar energy conversion

Abstract: This work addresses the role of different modifiers on the overall photocurrent response, which allowed a dual material insertion, increasing the charge separation without compromise the surface catalysis. Sn-addition onto nanoceramic hematite photoelectrodes clearly increased flat band potential, promoting a good charge separation, and shifting the onset to a higher potential, attributed to the surface-trapping state created by this modification. Notoriously, Sn-hematite photoelectrodes loaded with NiFeO x ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…We see surface states, ruled by the Fe-d and O-p orbitals hybridization, appearing within the bulk energy gap in all slab calculations, which can serve as hole traps [24]. This prediction goes according to recent experiments where NiFeOx act passivating those surface states, where the pristine character of the surface has been restored by the suppression of the hole traps [25].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…We see surface states, ruled by the Fe-d and O-p orbitals hybridization, appearing within the bulk energy gap in all slab calculations, which can serve as hole traps [24]. This prediction goes according to recent experiments where NiFeOx act passivating those surface states, where the pristine character of the surface has been restored by the suppression of the hole traps [25].…”
supporting
confidence: 82%
“…Therefore, the photocurrent is proportional to the transmission rate of the electrons between grains. Astonishingly, the experimental increase of the photocurrent occurs by a factor of 2 for Sn doped [25] and 6.5 for Sb doped [6], at the same order of the values predicted by our approximated model. Such microscopic interpretation allows us to understand and predict quite reasonably the experimentally observed increase of the photocurrent upon Sn/Sb doping.…”
supporting
confidence: 82%
“…A major effort in the community is to understand the surface reactions and transport properties of hematite photoanodes. Numerous methods have been employed to improve the oxygen evolution reaction (OER) efficiency such as oxygen vacancies incorporation, doping engineering ( in situ and ex-situ ), and high-temperature treatments. Many of these methods enhance the PEC performance of hematite via surface modification. Previous reports have demonstrated that intentional doping with Sn or Sb can significantly increase the carrier density of hematite, favoring an efficient charge separation and thus its photocatalytic performance. , Some of these surface modifications successfully promote OER by accelerating the photogenerated charge transfer and reducing the charge resistance at the solid–liquid interface. ,, …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the literature propositions, it is well-known that for thicker materials surface modifications do not have a drastic impact on the metal oxide-substrate interface and often present major positive effects related to the solid–liquid interface. , However, for thinner layers, there is a greater interaction between the layer and the substrate, which can approach the material being composed only of the surface. , In this sense, the mechanical stress involved in the hydroxylation process can significantly affect all homo- and/or heterointerfaces of different thicknesses, achieving opposite results. Hydroxylation might contribute to or accumulate effects that negatively affect the photoanodes efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation